Hubungan Pengetahuan dan Sikap Warga Sekolah dalam Penanganan Tersedak pada Anak di SD Muhammadiyah Pendowohardjo - Fadhela Efrilia; Astika Nur Rohmah; Gatot Suparmanto (Lembaga Pengembangan Kinerja Dosen, 2025)
Choking is a condition where the airway is blocked by a foreign object, which can cause difficulty breathing and may lead to death. Proper techniques such as back blows, chest thrusts, and the Heimlich maneuver are essential in handling such situations. Therefore, it is important for school members to have adequate knowledge of choking first aid so they can respond quickly and accurately when a child is choking. This study aims to determine the relationship between school members' knowledge and attitudes in handling choking incidents in children at SD Muhammadiyah Pendowohardjo. The research used a quantitative approach with a correlational design and a cross-sectional method. A total of 30 respondents were selected using the total sampling technique. The instruments used were knowledge and attitude questionnaires. The results showed that 26 respondents (86.7%) had good knowledge, and 21 respondents (70%) demonstrated good attitudes in handling choking incidents. Statistical analysis using the Spearman rank correlation test revealed a significant relationship between knowledge and attitude, with a p-value of 0.001 (<0.05) and a correlation coefficient of 0.631. This indicates a strong relationship between school members' knowledge and their attitudes in handling choking in children.